Soil Fungal Community in Grazed Inner Mongolian Grassland Adjacent to Coal-Mining Activity - Xie, Linlin; Bi, Yinli; Li, Xianglei; Wang, Kun; Christie, Peter (Frontiers in Microbiology, 2021)
Coal mining results in reduced soil quality and makes environments less stable. Soil fungi are suitable indicators of soil quality for monitoring purposes. Here, the objective was therefore to investigate the effects of grazing and mining on the composition of the soil fungal community at the periphery of an opencast coal-mine dump in the Shengli mining area, Xilingol League, Inner Mongolia. A total of 2110 fungal operational taxonomic units (OTUs) were identified and subdivided into 81 orders and nine categories, based on trophic modes. The sensitivity of soil factors to coal-mining and grazing was differently. The sensitive factor to mining was soil pH, and that to grazing were soil nitrate-nitrogen and alkaline phosphatase activity. According to the Pearson correlation and Mantel test, we propose interactions between grazing and coal-mining exist a co-effect and could regulate edaphic variables to alter the behavior of soil fungal community. Moreover, compared with coal-mining, grazing has a greater impact on it. The results provide a basis to further clarify soil fungal ecological functions, and may also contribute to the practice of soil remediation and environmental management in coal-mining areas.